(3GJUGdGJ GdefXeGJ YHQ hSGFd GdJhGUd GdMOjKI (B/s - (3WfWGhj, ejQgGf eMSfs ((3GdbGgQI (B:s (3OGQ GdYGde GdYQHj ,s, 2020)
(3jMJhj gPG GdcJGH Ydi CQHYI aUhd eNJdaI JJfGhd YOOG ef GdehVhYGJ GdNGUI HEOGQI GdGJUGdGJ aj GdefXeGJ GdMOjKI h Pdc ef NdGd JhXja GdefXeGJ dehGbY GdJhGUd GdGLJeGYj aj OYe GdGJUGdGJ GdGSJQGJjLjI eY YedGFgG h Pdc ef NdGd GdJfhjY aj GSJNOGe GJUGdGJ GdefXeI eKd SeYI GdefXeGJ (B, (3GdeSDhdjI GdGLJeGYjI (B,(3EOGQI GdCReGJ (B, (3EOGQI YdGbGJ GdYedGA h ef gPG GdefWb GgJeJ GdHGMKI aj GdaUd GdChd HGdJYQa Ydi GdGSJQGJjLjGJ GdGJUGdjI ddefXeGJ YHQ ehGbY GdJhGUd GdGLJeGYj aj EOGQI SeYJgG(B- (3TQWI OHj fehPLG(B-(3h aj GdaUd GdKGfj GgJeJ GdHGMKI HGdJYQa Ydi OhQ ehGbY GdJhGUd GdGLJeGYj aj OYe GJUGdGJ GdeSDhdjI GdGLJeGYjI dTQcI WjQGf GdGJMGO (B, (3CeG GdaUd GdKGdK aJfGhd GSJQGJjLjGJ GdGSJLGHI GdGJUGdjI ddCReGJ h OhQgG aj MeGjI SeYI GdYdGeI GdJLGQjI ddefXeGJ (B...(3JWHjbGJ Ydi CReGJ HYV TQcGJ GdWjQGf GdYQHjI h GdYGdejI aj Mjf GgJe GdaUd GdQGHY HOQGSI aGYdjI EOGQI YdGbGJ GdYedGA YHQ hSGFd dGdJhGUd GdGLJeGYj (B...(3HGdJWHjb Ydi TQcI JhjhJG(B. s
Keywords: (3GdJhGUd GdGLJeGYj s; (3GdajSHhcs